A structural model for drawing: Investigating mark-making through Choreology. Issue 1 (1st April 2022) - Oppenheim, Leonora
A structural model for drawing articulates the elements that come together to produce mark-making. This model was inspired by Choreology, the study of movement initiated by dance artist and educator Rudolf Laban in the first half of the twentieth century. Laban developed theories for movement to help dancers better understand the expressive potential of their bodies. His analysis, together with subsequent scholars, defines how the human body moves in space. In the way dancers and choreographers gain analytical skills and greater awareness of their movement choices through studying Choreology, so visual artists can gain a new understanding of mark-making and its relationship to the body by looking at drawing through the lens of movement theory. This project was carried out during my research in Creative Practice at Trinity Laban Conservatoire of Music and Dance, 2017‐19. In the process of developing the model for drawing, I created a palette of marks by testing out a range of movements with different mark-making tools such as pens, pencils, watercolours and paint sticks. These marks correspond to Laban's Effort Actions, a list of eight physical actions the body can make. The resulting artworks have a particular energy and visual language to them. Their creation is driven by the way the mark-maker moves their whole body in a choreographed drawing performance. Through physical actions, the mark-maker becomes aware that specific movements make specific marks. The appearance of these marks is influenced by the form and the effort of the physical movement, by the surface material, its orientation, and by the mark-making instrument and its colour. Designing a structural model for drawing has given me a deeper insight into the process of embodied drawing and performance, enabling me to make informed choices about the visual traces I create through moving my body in different ways.